Innovation Agility and Its Role in Advancing Educational Outcomes: Systematic Review of Future Research Directions - Hariyanto, Hariyanto; Rahayu, Agus; Hadi Senen, Samsul; Adi Wibowo, Lili (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
This systematic bibliometric review examines the relationship between innovation agility and institutional performance in the field of education. In the context of globalization and rapidly evolving learning demands, educational institutions must adapt and innovate to remain relevant and effective. Using the Scopus database, this study analyzes research publication and citation trends from 1998 to 2025. The findings reveal a growing scholarly interest, particularly since 2019, with 45 articles published in 2024 alone. Recent studies emphasize themes such as digital transformation, agile learning environments, and the integration of technology in educational management. However, gaps remain regarding the role of information technology capabilities in shaping innovation-driven educational outcomes. This review highlights the critical importance of fostering innovation agility within education systems to enhance institutional performance, teaching effectiveness, and student learning outcomes. Future research directions should explore how innovation and agility interact with external factors such as policy, technology adoption, and global educational trends. Understanding these dynamics will equip educators and policymakers to navigate challenges and promote sustainable educational excellence.